Revisiting the thermodynamic properties of the LiCl–NaCl–KCl–H2O quaternary and its sub-ternary systems at 298.15 K. (September 2015) - Yang, Haitang; Zeng, Dewen; Chen, Yifeng; Xiao, Li; Du, Yong
Abstract: The phase diagram of the quaternary system LiCl–NaCl–KCl–H2 O have been predicted with a Pitzer–Simonson–Clegg thermodynamic model by combining the binary and ternary model parameters, which were determined by simulating reliable experimental data. The predicted phase diagram shows a good agreement with the available experiment data from the literature. The other thermodynamic properties (e.g. water activity) of the quaternary and its sub-ternary systems have been investigated by the model and compared with the experimental data in literature. Significant improvements have been made in comparison with assessments. Highlights: We simulated the thermodynamic properties of system LiCl–NaCl–KCl–H2 O by PSC model. The predicted phase diagram of the titled system agrees well with experiment data. The predicted water activity was compared with experiment data from literature. The accuracy of the experimental data from literature has been evaluated.